Ethics for journalists [electronic resource] - Keeble, Richard , 1948- (New York, NY : Routledge, 2009)
Tackles many of the issues which journalists face in their everyday lives - from the media's supposed obsession with sex, sleaze and sensationalism, to issues of regulation and censorship. This book
1. Ethical Controversies Today: An Overview -- 2. Regulating the Mainstream Media: Dawdling in the Last Chance Saloon? -- 3. At the Root of Relationships: Sourcing Dilemmas -- 4. The Ethics of Sleaze Coverage: Privacy, Bugging, Surveillance and Subterfuge -- 5. Dumbing Down or Dumbing Up? The Tabloidisation Controversy -- 6. Challenging the Gender Agenda -- 7. Getting the Representation Right -- 8. Battling for the News: the Dilemmas of War Reporting (and Not Just on the Frontline) -- 9. Constraints on Journalists -- 10. The Ethical Challenge: How You May Respond -- 11. And Finally: More Useful Websites and Blogs. Bibliography. Index
Description based on print version record
Includes bibliographical references and index
Keywords: Journalistic ethics